L'accès inégalitaire des femmes à la propriété foncière en république du Bénin : mise en perspective du décalage entre droit étatique et droit coutumier - Djima Radji, Asmaou A. A. A. (Université du Québec à Montréal, 2022)
L’accès des femmes aux ressources foncières en Afrique, et plus particulièrement au Bénin, demeure une question fondamentale. Pourtant, maillon clé du développement économique et social béninois, les droits fonciers des femmes se trouvent limités par l’application de règles coutumières, que renforce une certaine ineffectivité du droit étatique. Ce mémoire a pour objectif de faire une mise au point sur cette concurrence des normes en matière d’accès à la propriété foncière des femmes. En effet, en milieu rural, la vie tant sociale que juridique est majoritairement gouvernée par des pratiques coutumières. Alors que les femmes participent activement à la vitalité économique du pays, notamment en cultivant la terre, elles restent discriminées dans l’accès à la propriété des ressources foncières. Cet état des lieux constitue le point d’ancrage de ce mémoire. Il s’agira de comprendre l’effet de cette dualité juridique et de proposer quelques suggestions susceptibles de favoriser l’accès des femmes béninoises à la propriété foncière. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : femme.s, propriété foncière, accès, terre, droit coutumier, droit étatique, droits fonciers, Bénin, Afrique, Afrique de l’Ouest
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; afrique; biblioFem*; bénin; discipline; discriminations; droit; droits des femmes*; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; thématiques

Climate–urban nexus: A study of vulnerable women in urban areas of KwaZulu-Natal province, South Africa - Hlahla, Sithabile; Simatele, Mulala Danny; Hill, Trevor; Mabhaudhi, Tafadzwanashe (Weather, Climate, and Society, 2022)
The changes in climatic conditions and their associated impacts are contributing to a worsening of existing gender inequalities and a heightening of women’s socioeconomic vulnerabilities in South Africa. Using data collected by research methods inspired by the tradition of participatory appraisals, we systematically discuss the impacts of climate change on marginalized women and the ways in which they are actively responding to climate challenges and building their adaptive capacity and resilience in the urban areas of KwaZulu-Natal, South Africa. We argue that changes in climate have both direct and indirect negative impacts on women’s livelihoods and well-being. Less than one-half (37%) of the women reported implementing locally developed coping mechanisms to minimize the impacts of climate-related events, whereas 63% reported lacking any form of formal safety nets to deploy and reduce the impacts of climate-induced shocks and stresses. The lack of proactive and gender-sensitive local climate change policies and strategies creates socioeconomic and political barriers that limit the meaningful participation of women in issues that affect them and marginalize them in the climate change discourses and decision-making processes, thereby hampering their efforts to adapt and reduce existing vulnerabilities. Thus, we advocate for the creation of an enabling environment to develop and adopt progendered, cost-effective, transformative, and sustainable climate change policies and adaptation strategies that are responsive to the needs of vulnerable groups (women) of people in society. This will serve to build their adaptive capacity and resilience to climate variability and climate change–related risks and hazards. © 2022 American Meteorological Society.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afrique du sud; approches et analyses; changements climatiques; environnement; histoire et politique; patriarcat; pauvreté; projet charge mentale; périodes historiques; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques